1974
DOI: 10.5935/0305-7518.19740015
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of the Nose in Lepromatous Leprosy

Abstract: l. l. Group of Hospita is, Bombay, lndia Forty-five scrotal skin and underlying dartos biopsies from leprosy patients of varying types, duration and treatment status were examined for quantitative bacteriology and qualitative histology. 33% on homogenization and 34% on histology were positive for acid fast bacilli. The average bacillary loadjg of positive tissue was 1.5 X 10 7 45% of scrotal biopsies were positive against 42% of the skin patch when examined for qualitative changes diagnostic of leprosy. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1
8

Year Published

1975
1975
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 1 publication
0
41
1
8
Order By: Relevance
“…In addition to infiltration and presence of blood on the mucosa of nasal cavities, we could identify the presence of crusts (Photos 1, 2 and 4) at the nasal endoscopy of 54 patients, representing 31.2% of the 173; it was also a frequent finding in the study by Barton (1974) 5 , who found it in 74% of the 77 studied patients, by Fokkens et al (1998) 22 , who found 62% among the 40 studied patients, and by Srinivasan Photo 1. LL presentation with septal anterior-inferior damage, presence of vasculitis, dryness, infiltration, mucosa hyperemia, crusts and blood spots.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In addition to infiltration and presence of blood on the mucosa of nasal cavities, we could identify the presence of crusts (Photos 1, 2 and 4) at the nasal endoscopy of 54 patients, representing 31.2% of the 173; it was also a frequent finding in the study by Barton (1974) 5 , who found it in 74% of the 77 studied patients, by Fokkens et al (1998) 22 , who found 62% among the 40 studied patients, and by Srinivasan Photo 1. LL presentation with septal anterior-inferior damage, presence of vasculitis, dryness, infiltration, mucosa hyperemia, crusts and blood spots.…”
Section: Discussionmentioning
confidence: 90%
“…3,[5][6][7] We can also note the importance of nasal mucous in the transmission of the infection, which may be a primordial factor for the dissemination of the disease, but other paths may be involved. The nasal mucosa is considered as entry and exit doors for Mycobacterium leprae in many cases considering how vulnerable the openings are and the free access to the bacilli.…”
Section: Chacko Et Al (1979)mentioning
confidence: 99%
See 2 more Smart Citations
“…36 However, because a single dose of 100 mg dapsone results in serum and tissue drug concentrations that are approximately 500-fold in excess of its minimal inhibitory concentration against My cobacterium Zeprae and since the relatively long half-life of dapsone is such that inhibitory con centrations of the drug are probably maintained for about 10 days,28 it is clear that the failure to self-administer dapsone must be extremely prolonged before it results in clinical and bacteriological relapse caused by the renewed multi plication of fully dapsone-sensitive M. Zeprae. Such a conclusion is strengthened by the observation that over the short term the response of a small group of patients treated with a dose of 1 mg dapsone/day was indistinguishable from that routinely observed with standard 50 or 100 mg daily dosesY…”
Section: Therapeutic Implications Of Poor Dapsone Compliancementioning
confidence: 99%